PENINGKATAN HASIL BELAJAR PPKN MELALUI MODEL NHT BERBANTUAN MEDIA SMART BOX DAN VIDEO PADA SISWA KELAS III SEKOLAH DASAR - Mokhamad Aminudin; Muhammad Aunur Rofiq; Anna Mariyani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The background of this study is the low learning outcomes and learning activeness of third grade pupils in Civic Education (PPKn) at SDN 2 Ketileng. The learning activities were still teacher-centered and did not incorporate new media; thus, the students were passive in the lessons. This research was conducted to increase student learning outcomes and activeness by applying the Numbered Head Together (NHT) model supplemented by smart box media and video. This study used Classroom Action Research in two cycles with the number of students 21. Data were acquired through testing, observations, interviews and documentation. Results showed that the introduction of NHT model with smart box and video media helped in improving the learning outcome and activeness of the students. The mastery of learning was increased from 42.86% in the pre-cycle, to 66.67% in cycle I, and 85.71% in cycle II. The students’ activeness also rose from cycle I (80.95%) to cycle II (100%). Students were more eager, confident and engaging in discussions and presentations. NHT model helped smart box and video media may be employed as an innovative learning alternative in primary school.